Importance And Contents Of Business Plan: A Case-Based Approach - Ruqayah Abdullah (Jurnal Manajemen Indonesia, 2020)
Planning and business plan, as a its product represent essential part of the overall business management. The business plan covers all important aspects of the business and the key factors that affect its performance. The business plan is used to increase the opportunities for development, growth and raise additional capital. This paper discusses the importance of business plan, its contents and provides some rules that should be taken into consideration during its writing, etc. In this paper is used the case-based methodology, where a practical example of a business plan is provided. The paper ends with discussion and conclusion section and limitations, practical implication and future research avenues as well. Keywords— planning; business pan; entrepreneur; marketing; capital